Prognostic significance of CNSL at diagnosis of childhood B-cell acute lymphoblastic leukemia: A report from the South China Children’s Leukemia Group - Xu, Lu-Hong; Geng, Xu; Liao, Ning; Yang, Li-Hua; Mai, Hui-Rong; Wan, Wu-Qing; Huang, Li-Bin; Zheng, Min-Cui; Tian, Chuan; Chen, Hui-Qin; Chen, Qi-Wen; Long, Xing-Jiang; et al. (Frontiers in Oncology, 2022)
Objectives: The prognostic significance of acute lymphoblastic leukemia (ALL) patients with central nervous system leukemia (CNSL) at diagnosis is controversial. We aim to determine the impact of CNSL at diagnosis on the clinical outcomes of childhood B-cell ALL in the South China Children’s Leukemia Group (SCCLG). Methods: A total of 1, 872 childhood patients were recruited for the study between October 2016 and July 2021. The diagnosis of CNSL was dependent on primary cytological examination of cerebrospinal fluid, clinical manifestations and imaging manifestations. Patients with CNSL at diagnosis received two additional courses of intrathecal triple injections during induction. Results: The frequency of CNLS at diagnosis of B-cell ALL was 3.6%. Patients with CNSL at diagnosis had significantly higher mean presenting leukocyte count (P=0.002) and poorer treatment response (P < 0.05) compared with non-CNSL patients. Moreover, CNSL status was associated with worse 3-year event-free survival (P=0.030) and higher risk of 3 year-cumulative incidence of relapse (P=0.008), while no impact was observed on 3-year overall survival (P=0.837). Multivariate analysis revealed that CNSL status at diagnosis was an independent predictor with higher cumulative incidence of relapse (hazard ratio=2.809, P=0.016). Conclusion: CNSL status remains an adverse prognostic factor in childhood B-cell ALL, indicating that additional augmentation of CNS-directed therapy is warranted for patients with CNSL at diagnosis.